Pengaruh Kompensasi, Kepemimpinan terhadap Etos Kerja dengan Kepuasan Kerja sebagai Intervening: Studi pada Hotel Sartika Yogyakarta - Fathurrahman, Puri Muhammad; Kirana, Kusuma Chandra; Subiyanto, Didik (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study was to determine the effect of compensation, leadership, on work ethic and determine the effect that occurs indirectly on job satisfaction which acts as a mediator in Hotel Sartika. The method used in this research is quantitative. Primary data from a questionnaire with 50 respondents using the saturated sample method, where all members of the population will be sampled. The validity and reliability tests were used by researchers to test the quality of the data, with data analysis. The techniques used were the classical assumption test, multiple linear regression test, hypothesis testing and sobel test. Based on the results of the research that has been done, this shows that compensation does not have a positive and significant effect on work ethic, leadership does not have a positive and significant effect on work ethic, compensation has a positive and significant effect on job satisfaction, leadership has a positive and significant effect on satisfaction job, satisfaction has a positive and significant influence on work ethic. Keywords: Compensation, Leadership, Work Ethic, and Job Satisfaction